Análise da distribuição dos potenciais tubo/solo em gasodutos enterrados de aço carbono API 5L protegidos catodicamente por corrente impressa: influência da proximidade do leito de ânodos - DIAS, Lázaro Machado (2015)
This work aims at analyzing the settings of the cathodic protection system of the Bahiagás pipeline system, for its great importance, due to the installation of carbon steel pipelines near urban areas. In this sense, there have been difficulties during its construction due to interference, in its guideline and in the choice of a safe location for installing the anode bed, related to the observance of the distances between the latter and the protected duct, in order to meet a practice that is recommended by cathodic protection professionals in Brazil. Given such difficulty, together with the vehement need to reduce the cost of cathodic protection installation, this research proposes the analysis of the influence of the proximity of the carbono steel land pipelines and the anode bed, taking into account the physical, chemical and microbiological characteristics of the soil. We have applied systematic methodology in identifying the cathodic protection level in rectifiers, near the anode bed and along the route of the pipeline, the object of analysis, with the following equipment was used: high precision millivoltmeter, GPS system, and receiving antenna, 02 (two) Cu/CuSO4 reference electrodes, 02 (two) fiberglass rods for the extension of the electrodes, waist-attachable spool with odometer and bare copper coil with a 2-kilometer length, installation of an automatic ON/OFF key, synchronized via satellite, to turn on and off, within a fraction of second, before the occurance of depolarization. We measured the soil resistivity and proceeded to the physical, chemical and microbiological classification of the soil, through samples collected at 0 to 1.6m profile, at intervals of 20 cm, through excavation, borehole, using a Dutch auger, whose bucket had the following features: 20-cm height, 6-cm diameter and 560-cm3 volume. These samples were sent to the laboratories of Embrapa and UFRB for the analysis of electrical conductivity, texture, density, grain size, pH organic matter, cations, anions, V = sum of bases, CEC = cation exchange capacity. As a result, the analyzis of the level of influence of the proximity of the anode bed to a buried pipeline for the distribution of potential pipe-soil, considering soil variables, such as electrolyte, shows that, despite the variables involved, there is a reasonable amount of uniformity. The perpendicular distance between the first anode and the pipeline, analysed in this study, were: 58m in the range of Polo I Pipeline, 17m in the range of Tronco-Feira Santo Amaro Pipeline, and 28m in the range of Candeias Pipeline. The results do not support the recommendation given by the Brazilian Cathodic protection professionals, which is 100m, indicating possible flexibility to enable the safe expansion of the gas pipeline network in urban areas, with lower costs and higher feasibility of cathodic protection installation, not being restricted to a 100-m distance, which is often not feasable.